Improvement of Endoscopic Reports with Implementation of a Dictation Template. Issue 1 (19th December 2019) - Harris, Natasha; Telford, Jennifer; Yonge, Jordan; Galorport, Cherry; Amar, Jack; Bressler, Brian; Brown, Carl; Lam, Eric; Nap-Hill, Estello; Phang, Terry; Ramji, Alnoor; Suzuki, Matthew; et al.
Abstract: Aims: Completeness of procedure reports is an important quality indicator in endoscopy. A dictation template was developed to ensure key elements were included in colonoscopy and esophagogastroduodenoscopy (EGD) reports. Endoscopy reports were reviewed prior to and following implementation of the dictation templates to determine whether report completeness improved. Methods: Key elements in an endoscopic report were identified from published guidelines and posted at dictation stations. Colonoscopy and EGD reports were reviewed for the nine physicians performing endoscopy at St. Paul's Hospital prior to and following implementation of dictation templates. Dictation completeness was defined as inclusion of all key elements. Dictation completeness and inclusion of individual key elements at the two time points were compared using the t -test and Chi-square test. Results: Reports for 4648 procedures undertaken by nine endoscopists were reviewed for completeness at each time point (2008 and 2014). Colonoscopy report completeness increased from 65.8% to 83.2% ( P < 0.001). Items that improved included documentation of consent, endoscope used, complications, withdrawal time and rectal retroflexion. EGD report completeness increased from 72.7% to 77.3% ( P < 0.001) with improvement in documentation of consent and complications. Items consistently underreported for colonoscopy and EGD at both time points included: patient age, comorbidities, current medications and patient comfort. Conclusion: There was an association between the use of a posted dictation template at dictation stations and the improved completeness of endoscopic reports.